Antifungal Effect of Cinnamon Bark Extract on the Phytopathogenic Fungus Fusarium sporotrichioides - Katarina Martinko; Eni Mioč (Food Technology and Biotechnology)
Research background. The use of plant extracts in the biological control of fungal plant diseases can reduce the use of fungicides and residues in food by effectively suppressing mycotoxigenic microorganisms. The focus of interest is therefore finding plant extracts that have antifungal properties and are not toxic to organisms, so that they can be used for the biological control of economically important phytopathogenic fungi such as Fusarium. Species of the genus Fusarium are considered economically important pathogenic fungi of numerous agricultural crops, which not only cause significant losses but also produce mycotoxins that reach consumers through food. One of the most important species of this genus is the species Fusarium sporotrichioides, which causes economically significant damage to a large number of agricultural crops. Experimental approach. In this laboratory study, the influence of aqueous cinnamon bark extract on the growth and development of the toxicogenic fungus F. sporotrichioides was investigated using the poisoned food technique. For the study, the aqueous extract of cinnamon bark was obtained by ultrasound-assisted extraction and the content of antifungal compounds was detected by phytochemical tests. Results and conclusions. The research results confirm a significant inhibition of the growth of the pathogen when grown individually on a potato-dextrose agar (PDA) medium with 3 and 5 % extract. The antifungal effect of the extract was demonstrated by microscopic analysis of the pathogen, which showed significant deformation of hyphae and a change in the mycelium colour after seven days of growth on medium with 5 % extract, resulting in a threefold higher inhibition of pathogen growth than growth on medium with 3 % extract. The microscopic changes also show a reduction in pathogen sporulation and a possible reduction in mycotoxin production. Phytochemical tests confirmed the presence of antifungal compounds in the extract. Novelty and scientific contribution. Based on the obtained results, the aqueous extract of cinnamon bark shows a fungistatic effect on the growth and development of F. sporotrichioides, which opens the possibility of continuing research of cinnamon compounds as potential compounds of future control agents for the suppression of fungi of the genus Fusarium.